Effect of export experience and market scope strategy on export performance: Evidence from Poland - Jerzy Cieślik (2018)
© 2015 Elsevier Ltd. This study examines the impact of internationalization experience and market scope strategy on the export performance of firms operating in Poland. This study uses data from 2003 to 2010, an eight-year period that includes the country's accession into the European Union in 2004. Several important findings are revealed by the research. First, a firm's export experience and performance have an inverted S-shaped relationship, i.e., performance is increasing at low and high levels but decreasing at moderate levels of experience. Second, the relationship between the growth of the number of export countries and export performance is initially positive, but becomes negative over time. Third, over time the growth of a firm's share of the main export market is found to be negatively related to export performance. Revealing the dynamism of these relationships through a longitudinal approach is of theoretical and practical importance to scholars, practitioners and governments of other emerging economies that are considering joining similar trade organizations/agreements.